La estimativa jurídica de los cargos de confianza - Godenzi Alegre, Jorge Luis (2019)
Our legal system, starting with the Magna Carta, establishes protection and guarantees for the worker who may be the victim of arbitrary dismissal. He makes no distinction when he makes that reference; However, we are faced with a thorny problem when the particularity of an employment relationship arises that suddenly concludes by exclusive decision of the employer, by claiming this, as a justification for that arbitrary dismissal, the loss of confidence that the worker raises. It's that simple.  There is the question that we are going to develop in this article, which does not depend on internal legislation (Supreme Decree No. 003-97-TR, Law on Labor Productivity and Competitiveness and others) or on the varieties that constitute some plenary decisions of the Supreme Court or judgments of the Constitutional Court, but to analyze this issue from the theoretical and practical reason, without discrimination, or differentiated facts that are worth, no matter how nuances the judges have finally found in their resolutions, because not only the discretion of the decision the employer makes; It seems to me, in any case, that I should always carry it out with prudence, reasonableness and respect for the fundamental rights of any worker.  The reality in the workplace is very active, but the balances are accelerating and the complexity of today's transformations imposes us to rethink how we estimate trust positions. It will be better to get used to it: seasons are coming when that word will never be as before.